A comparative study of British and Indian informal activities of girls. - et. al., Nikita Sukare, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research study aims to investigate the informal social activities of youth age girls in England and in India . Culture has been perceived to be the pivot point on which human beings peg their socialization orientation and characterization (Piranha, 2009). However, with the current trends, including globalization and technological advances, it is hypothesized that the world’s youths engage in similar informal activities. This research therefore, tries to prove the hypothesis of whether girls informal activities are the same in a secular society and a closed society; England and India respectively. The aim of this study is to critically examine the similarities and differences between Indian and English young girls with regard to how they spend their free time in their respective countries. It aims to address these issues from a historical as well as current view points and tries to postulate how long the activities will still be pegged on regions and cultural orientations of the society. The research will examine these trends and endeavor to explain the reasons why the differences still exist or what has made them erode. India and England have unique differences in terms of their histories, economic power, level and type of education, cultural orientation, population and lifestyles (Piranha, 2009). This research therefore, attempts to investigate how these themes constitute the development of policies for the young girl. The way children, and girls in particular, are raised in Indian and English societies will be investigated to establish a link between the upbringing and the girls’ future development.